PELATIHAN ECO ENZYME BAGI IBU AISYIYAH UNTUK EKONOMI SIRKULAR BERKELANJUTAN KABUPATEN BUNGO - Karlinda, Karlinda; Yulda, Apri; Firnanda, Icha Wieke; Ramadhani, Mutiara (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The increase in global waste generation has serious impacts on health and the environment. Utilizing organic waste into eco-enzymes—an environmentally friendly multipurpose liquid—is an innovative solution. This activity aims to empower the Aisyiyah women's group in managing organic waste economically and sustainably. The method is based on community empowerment through FGDs, socialization, training, mentoring, and evaluation. The results show an increase in the Aisyiyah women's group's knowledge about eco-enzymes, which was initially only 37.89% to 75.00%. Furthermore, the skills in making eco-enzyme fermentation liquid also increased by 45.78%, from 32.43% to 70.32%. Participants' skills and motivation to produce eco-enzymes independently. Awareness of the circular economy also increased. This activity contributes to waste reduction, increased environmental awareness, and the strategic role of women in sustainable waste management.